(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2024)
The study examines the effect of test anxiety on students’ performance in Mathematics. Four Hundred (400) students’ were randomly selected and Forty (40) students’ were purposively selected from Ten (10) schools which comprised of five (5) schools each from private and public school. Three (3) general questions were formulated and answered descriptively while three hypotheses in the study were t-test statistics. The result showed there was no significant difference in the mean of observable test and anxiety behavior between JSS II and SS II students. Also, students’ gender and class did not have any significant influence on their test anxiety level while school type significant influenced anxiety level and thus academic performance in Mathematics among the sampled secondary schools in Ikere Local Government Area in Ekiti State. The study recommended that students’ perception of Mathematics should be enhanced through teachers genuine interest in developing their students’ Mathematical competencies. Mathematics teachers should alleviate the fear of their students by emphasizing that mathematics is not a difficult subject. Also, teachers and students’ perception of mathematics should be changed through the creation of an enabling environment in term of infrastructural and other materials that can enhance the teaching and learning of Mathematics.